(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The economics of sustainable development (ESD) focuses on the ecological, economic and social dimensions of the society of the future. Conceptual foundations (ESR): elimination of the existing model of development, its replacement by the paradigm of sustainable development, the need for personal limitations, the use of technologies that ensure the long-term preservation of raw materials, the improvement of the quality of human life, the introduction of a market economy system with socio-ecological limitations due to the use of political and legal instruments , analysis of economic processes through the use of an interdisciplinary approach taking into account social and environmental dependencies. It was established that the transformation of an industrial society into a sustainable one requires the use by enterprises of the following development strategies: efficiency strategies (increasing the efficiency of resource use); cohesion strategies (development of products that meet the requirements of sustainable development); limitation strategies (voluntary decision of people to change their lives, shaping them accordingly to the principle of internal and intergenerational justice). Strategies of efficiency and cohesion are usually implemented by commercial - socially responsible enterprises, the strategy of limitation - by non-commercial ones. It has been proven that the universal tool for the implementation of all strategies by the enterprise is marketing, which is oriented towards conscious consumption, takes into account the point of view of the consumer, producer, and society and ensures the receipt of complex economic, ecological, and socio-cultural benefits. It is substantiated that due to the depletion of the Earth’s resources, the rapidly growing population, it is not enough for commercial enterprises to use only strategies of efficiency and cohesion to implement the ideas of sustainable development. New marketing complexes, in particular, "4C" and "SIVA" are tools aimed at the promotion and sale of goods with the benefit of the consumer. A combination of high costs and low benefits can be offered to enthusiasts of the idea of sustainable development. However, this group of consumers occupies a small niche. It is best to implement solutions that provide consumers with a combination of high benefits and low costs. For this, it is advisable to use new marketing complexes.